Spermatogenic Cell-Specific Gene Mutation in Mice via CRISPR-Cas9. (20th May 2016) - Bai, Meizhu; Liang, Dan; Wang, Yinghua; Li, Qing; Wu, Yuxuan; Li, Jinsong
Abstract: Tissue-specific knockout technology enables the analysis of the gene function in specific tissues in adult mammals. However, conventional strategy for producing tissue-specific knockout mice is a time- and labor-consuming process, restricting rapid study of the gene function in vivo . CRISPR-Cas9 system from bacteria is a simple and efficient gene-editing technique, which has enabled rapid generation of gene knockout lines in mouse by direct injection of CRISPR-Cas9 into zygotes. Here, we demonstrate CRISPR-Cas9-mediated spermatogenic cell-specific disruption of Scp3 gene in testes in one step. We first generated transgenic mice by pronuclear injection of a plasmid containing Hspa2 promoter driving Cas9 expression and showed Cas9 specific expression in spermatogenic cells. We then produced transgenic mice carrying Hspa2 promoter driven Cas9 and constitutive expressed sgRNA targeting Scp3 gene. Male founders were infertile due to developmental arrest of spermatogenic cells while female founders could produce progeny normally. Consistently, male progeny from female founders were infertile and females could transmit the transgenes to the next generation. Our study establishes a CRISPR-Cas9-based one-step strategy to analyze the gene function in adult tissues by a temporal-spatial pattern.